Pseudohypericin and Hyperforin in Hypericum Perforatum From Northern Turkey: Variation Among Populations, Plant Parts and Phenological Stages - Çirak, C.; Radušiene, J.; Janulis, V.; Ivanauskas, L. (Wiley, 2008)
Hypericum perforatum is a perennial medicinal plant known as "St. John's wort" in Western Europe and has been used in the treatment of several diseases for centuries. In the present study, morphologic, phenologic and population variability in pseudohypericin and hyperforin concentrations among H. perforatum populations from Northern Turkey was investigated for the first time. The aerial parts of H. perforatum plants representing a total of 30 individuals were collected at full flowering from 10 sites of Northern Turkey to search the regional variation in the secondary metabolite concentrations. For morphologic and phenologic sampling, plants from one site were gathered in five phenological stages: vegetative, floral budding, full flowering, fresh fruiting and mature fruiting. The plant materials were air-dried at room temperature and subsequently assayed for chemical concentrations by high performance liquid chromatography. Secondary metabolite concentrations ranged from traces to 2.94 mg/g dry weight (DW) for pseudohypericin and traces -6.29 mg/g DW for hyperforin. The differences in the secondary metabolite concentrations among populations of H. perforatum were found to be significant. The populations varied greatly in hyperforin concentrations, whereas they produced a similar amount of pseudohypericin. Concentrations of both secondary metabolites in all tissues increased with advancing of plant development and higher accumulation levels were reached at flowering. Among different tissues, full opened flowers were found to be superior to stems, leaves and the other reproductive parts with regard to pseudohypericin and hyperforin accumulations. The present findings might be useful to optimize the processing methodology of wild-harvested plant material and obtain increased concentrations of these secondary metabolites. © 2008 Institute of Botany, the Chinese Academy of Sciences.
Keywords: Hyperforin; Hypericum Perforatum; Population Variability; Porphologic and Phenologic Variations; Pseudohypericin